A Year of Israel’s Zionist Attack on Palestine (October 7, 2023-October 7, 2024): The Role of Global Peace Mission (GPM) Malaysia As A Humanitarian NGO - Hussin, Muhammad Khairul Iman; Saleh, Nor Zarifah (Journal Al-Muqaddimah, 2025)
The ongoing conflict in Palestine continues unabated. In fact, the holy land faced escalating pressure as the Israeli Zionist army launched a devastating attack on October 7, 2023, which persists to this day. According to the Palestinian Ministry of Health, the death toll for this war has reached a staggering 42,924 individuals, with 69 percent of them being women and children. Witnessing the deteriorating situation, Global Peace Mission (GPM) Malaysia, a humanitarian organization was mobilized to provide urgent assistance to the affected Palestinians. However, amidst their efforts, they encountered various challenges. Consequently, a qualitative study incorporating content analysis and historical methods was conducted to examine the role of GPM as a humanitarian organization and the challenges encountered during the relief mission. The findings revealed that GPM is a dedicated non-governmental organization that actively supports the Palestinian populace by addressing their immediate requirements, encompassing clothing, sustenance, medication, baby needs, and hygiene kits.